Microwave Wireless Power Transfer System Based on a Frequency Reconfigurable Microstrip Patch Antenna Array - Haiyue Wang; Lianwen Deng; Heng Luo; Junsa Du; Daohan Zhou; Shengxiang Huang (Energies, 2021)
The microwave wireless power transfer (MWPT) technology has found a variety of applications in consumer electronics, medical implants and sensor networks. Here, instead of a magnetic resonant coupling wireless power transfer (MRCWPT) system, a novel MWPT system based on a frequency reconfigurable (covering the S-band and C-band) microstrip patch antenna array is proposed for the first time. By switching the bias voltage-dependent capacitance value of the varactor diode between the larger main microstrip patch and the smaller side microstrip patch, the working frequency band of the MWPT system can be switched between the S-band and the C-band. Specifically, the operated frequencies of the antenna array vary continuously within a wide range from 3.41 to 3.96 GHz and 5.7 to 6.3 GHz. For the adjustable range of frequencies, the return loss of the antenna array is less than −15 dB at the resonant frequency. The gain of the frequency reconfigurable antenna array is above 6 dBi at different working frequencies. Simulation results verified by experimental results have shown that power transfer efficiency (PTE) of the MWPT system stays above 20% at different frequencies. Also, when the antenna array works at the resonant frequency of 3.64 GHz, the PTE of the MWPT system is 25%, 20.5%, and 10.3% at the distances of 20 mm, 40 mm, and 80 mm, respectively. The MWPT system can be used to power the receiver at different frequencies, which has great application prospects and market demand opportunities.